Genomewide admixture mapping of African cattle - Hirutu, Yonas Kassahun (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2011)
Genome-wide SNP analyses of cattle populations have become practical. In parallel, advanced and sophisticated statistical packages make it practical to extract embedded genetic information; for example differential levels of admixture across the genome. In this study, a Bayesian based statistical approach implemented for admixmre mapping analysis was used to examine Illumina 50k SNP genotype samples from the East (Ethiopian zebu) and West African (Borgou) hybrid zones. The analysis gave a quantitative measure of the degree of chromosomal mosaicism within the two hybrid zones, the dynamics of zebu genome introgression and identified regions with some evidence of the imprint of natural selection. 768 ancestry-informative SNPs from this high density bovine genotype data and other public resources were filtered for further work using a customised SNP assay.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin.